The importance of hydrologic refugia for the diversity of the Cape Flora - Nhlapo, Kagiso (Department of Biological Sciences, 2026)
Refugia are sites with more stable climate and hydrology than the surrounding area. There is growing recognition of the need to conserve refugia due to their role in harboring rare and endemic plants that might otherwise be prone to extinction due to global change. These sites are considered crucial for preserving species richness in the Cape Floristic Region (CFR) of South Africa, an area renowned for its exceptional plant species diversity and endemism, which is increasingly threatened by the impacts of global change. Despite the importance of refugia in the CFR, very little is known about their distribution. To fill this knowledge gap, I identify the distribution and character of refugia (mesic or xeric) by mapping total species richness (TSR), the distribution of widespread species (WS), narrow-range endemics (NREs), and wetland dependent narrow-range endemics (WD-NREs) and explore the environmental correlates of these distributions. I make use of Quarter degree square grid cells as a measuring unit, which are larger (~20 km across), than the scale at which microrefugia typically occur, however, the broad environmental heterogeneity within these units provides a meaningful basis for identifying potential refugial areas. From this study I find that the spatial distributions of TSR, WS, NREs and WD-NREs exhibited topographic and longitudinal gradients, with more species found in the southwestern CFR and in the mountains. Differences were observed in their correlates, where productivity, environmental stability explained TSR and WS, whereas environmental heterogeneity and environmental stability explained NREs and WD-NREs. Hydrological stability (such as groundwater-fed wetlands and seeps) and climatic stability (climatic stability index) have been documented to be indicators of refugia. Where hydrologic refugia provide broad-scale stable conditions for endemics and were found to play a significant role in maintaining persistence species in the CFR. These refugial sites face significant threats from groundwater abstraction, invasive species, and global change, highlighting the need for detailed fine-scale mapping and conservation of microrefugia within the broader refugial areas. Protecting these sites is essential for conserving biodiversity and ecosystem function in the CFR.